The fountain : a novel - Scieszka, Casey (Harper, an imprint of HarperCollins Publishers, 2026)
"Vera Van Valkenburgh hasn't been home in one hundred and eighty-eight years. But now Vera, forever twenty-six and able to heal from any wound, has returned to the Catskills. Whatever made her family immortal happened here, and if she can uncover it, maybe she can reverse it. After nearly two centuries--an endless sequence of unnoticed, meaningless lives and a soul-shaking incident in the desert--she longs to be released. Posing as a newly arrived forest ranger, she quickly blends into the upstate community and learns of something curious and disturbing. A mysterious, well-funded company is snapping up local property, no matter how high the asking price. But when her brother, a fellow immortal shows up, accompanied by a woman whose face is incredibly familiar to Vera, the purpose for her return gets clouded and Vera is in a race against time to find out what has caused her condition before someone else does"--